Recurrence of an Immature Thyroid Infiltrating Teratoma in a Female Infant - Bouzakri, Nabila; Lederer, Ann-Kathrin; Staubitz-Vernazza, Julia I.; Seidmann, Larissa; Pohlenz, Joachim; Siepermann, Meinolf; Musholt, Thomas J. (European Journal of Pediatric Surgery Reports, 2025)
This case report describes the recurrence of an immature thyroid infiltrating teratoma in a female infant. Initially treated surgically for a cervical mass, the teratoma recurred, requiring further intervention. The case highlights the importance of multidisciplinary care and long-term follow-up in managing complex pediatric neoplasms.
Keywords: teratoma; rare diseases; thyroid gland; dermoid cyst; newborn